Imagen y palabra a través de las mujeres medievales Segunda parte: Mujeres medievales en los reinos hispánicos - Arauz Mercado, DIANA (Escritura e Imagen, 2006)
Within the framework of peninsular Middle Ages and in concrete to begin the 17th Century regarding repopulation process in the course of conquest zones – we found the feminine presence of some Spanish queens whose work was notable inside her reigns, as the event of Sancha de León, Urraca de León y Castilla and María de Molina. This royal image will be complete to contribution of other centu- ry`s women whose beside to take part in political matters, leave her trace through the written word. Leonor López de Córdoba and Teresa de Cartagena are two examples of this work coming us enriching the medieval literature and demostrating once more the contribution of feminine`s legacy to the history.